2021
DOI: 10.1177/00027642211056268
|View full text |Cite
|
Sign up to set email alerts
|

Using Structural Topic Modeling to Explore the Role of Framing in Shaping the Debate on Liquefied Natural Gas Terminals in Oregon

Abstract: The drastic increase in domestic production of natural gas due to the fracking boom prompted efforts to develop a robust infrastructure in the U.S. to export natural gas. Given environmental concerns over increased fossil fuel development, significant opposition mobilized to “keep it [fossil fuels] in the ground” by acting to prevent not only natural gas production but also its transportation via pipelines and shipping via export terminals. Our analysis focuses on the latter component, specifically examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Dehler-Holland, Schumacher, and Fichtner 2021;Stelmach and Boudet 2021;Walter and Ophir 2021;Zhang, Wang, and Hu 2021) Therefore, through our qualitative inspection process detailed above, the frames popular in gun control or gun rights discourse can be distinguished. For instance, previous research has identified important frames within the gun control/rights discourse such as health activism(DeFoster and Swalve 2018, Zoller and Casteel 2021, McKeever et al 2022, mental health(Goss 2015), gun violence prevention(Jacobs 2002, McMillan andBernstein 2022), or many other frames(Fleming et al 2016;Cook and Goss 2020, Merry 2020) and apply these frames to our topics.…”
mentioning
confidence: 99%
“…Dehler-Holland, Schumacher, and Fichtner 2021;Stelmach and Boudet 2021;Walter and Ophir 2021;Zhang, Wang, and Hu 2021) Therefore, through our qualitative inspection process detailed above, the frames popular in gun control or gun rights discourse can be distinguished. For instance, previous research has identified important frames within the gun control/rights discourse such as health activism(DeFoster and Swalve 2018, Zoller and Casteel 2021, McKeever et al 2022, mental health(Goss 2015), gun violence prevention(Jacobs 2002, McMillan andBernstein 2022), or many other frames(Fleming et al 2016;Cook and Goss 2020, Merry 2020) and apply these frames to our topics.…”
mentioning
confidence: 99%